Interpretative model of shearband boudins internal evolution in HT ductile shear zones - Rodrigues, Benedito C. (2012)
The internal structure of a shearband boudin resulting from an original igneous, hydrothermal or metamorphic segregation tabular rigid body is a subject of scientific interest. It allows understanding the deformation mechanisms acting on homogeneous quartz aggregate activated during simple shear progressive deformation. This work is focused on the characterization of the internal evolution of shearband boudins, using microtextural analysis, fluid inclusions studies, fractal and OCP analysis. The proposed interpretative model shows the several structural stages that can be well established during the process of the internal evolution of shearband boudin.